Buck‐Boost‐Type MPPT Circuit Suitable for Vehicle‐Mounted Photovoltaic Power Generation. Issue 9 (1st July 2021) - Kano, Fumihisa; Kasai, Yuji; Kimura, Hideki; Sagawa, Kouhei; Haruna, Junnosuke; Funato, Hirohito
Abstract : This paper presents a buck–boost maximum power point tracking (MPPT) circuit suitable for solar cars. The MPPT controller, which consists of analog elements with a small number of complementary metal–oxide–semiconductor elements, achieved accurate tracking of the maximum power point of photovoltaic power generation and contributed to the power savings and weight reduction. A buck–boost dc–dc converter was adopted as the main power converter of the MPPT circuit to reduce the power‐conversion loss due to the wide voltage change in the battery. The 12 proposed MPPT circuits were installed in a solar car called '2019 Tokai Challenger' at an international convention and were shown to successfully generate sufficient solar power. © 2021 Institute of Electrical Engineers of Japan. Published by Wiley Periodicals LLC.